Application and efficiency of vitrification and electrokinetic techniques in soil remediation - Siveris, Wagner Luis; Vanzetto, Guilherme Victor; Immich, Gabriel; Thomé, Antônio (Ciência e Natura, 2019)
The improvement of remediation processes is necessary due to the impact caused by heavy metal ions and organic ionic compounds. Due to the lack of a universal method, several factors must be evaluated before choosing a technique. Vitrification and electrokinetics are soil remediation technologies that use the electrical potential to remediate. In vitrification the contaminant is immobilized in the soil, in electrokinetics, the contaminated material is separated from the soil. This bibliographical review had as main aim to approach vitrification and electrokinetics techniques in soils remediation. This review does not intend to exhaust the subject, but to approach the principles, application forms, advantages, disadvantages, efficiency, costs, and the application of the most cited methods in the literature. Vitrification has proven to be a safe technique, easy to apply and with good efficiency, however highly expansive. Electrokinetics proved to be more economically workable, with a variety of applications and with high efficiency.